Ensino de estatística descritiva: análise de tabelas e gráficos no ensino fundamental - Lima, Felipe Bruce de (2022)
The analysis of statistical data from tables and graphs is an important skill required of students. However, we identified there are several reports in the literature showing students’ struggle to read, interpret and position themselves when data are represented in tables and graphs. In view of this problem, our research aimed to structure a teaching-learning proposal for descriptive statistics, with a focus on data analysis from tables and graphs, considering 7th grade students as the target audience. This proposal is based on the current curriculum guidance documents (Common National Curriculum Base - BNCC and the Amazonas Curriculum Reference - RCA), as well as inspired by the approach of teaching Mathematics through Problem Solving. This research resulted in an educational product entitled "Analysis of Statistical Data from Tables and Graphs - An Approach to Mathematical Literacy in Elementary School II", which, inspired by the Delphi Method, was evaluated by an ad hoc committee, in the light of three dimensions - Novelty of the Product, Resolution that the product can allow and Elaboration and Synthesis. Considering the synthesis of the Ad hoc Committee evaluations, the data obtained allow us to infer the product met the requirements evaluated in the three dimensions, although it is necessary to obtain, in future work, information about the workload adequacy foreseen, understanding aspects that can be improved in the organization of the product to favor its replication by others. As far as the results referring to the three aforementioned dimensions are concerned, there is 75% agreement among the evaluators as to the educational product relevance in all dimensions. Thus, this study has shown that the educational product can have a positive impact on the teaching of Descriptive Statistics.